Teeth: their development and decay - McDowell, Sameul Alexander (My University, 1895)
Intoduction: Man in his most savage state, when his entire time was spent in roaming over the hills and through the valleys; did so that he might obtain something to eat. His entire end in this world was to supply his inner wants, and, in doing so, did he ever think of caring for those little organs, which make it possible for him to enjoy that food which his entire time was spent in capturing?
Citation: McDowell, Sameul Alexander. Teeth: their development and decay. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Man; Savage state; Hills; Valleys; Theses; Manuscripts (documents)